2018
DOI: 10.1021/acscatal.8b00787
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Studies of a Biocatalyst for the Enzymatic Production of Wax Esters

Abstract: Wax esters are high-value products whose enzymatic synthesis is of increasing biotechnological interest. The fabrication of cell factories that mass-produce wax esters may provide a facile route towards a sustainable, and environment-friendly approach to a large-scale process for this commodity chemical. An expedient route for wax-ester biocatalysis may be facilitated by the action of enzymes termed wax ester synthases/diacylglycerol acyltransferases (WS/DGAT), which produce wax esters using fatty acids and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(79 citation statements)
references
References 68 publications
3
76
0
Order By: Relevance
“…As average values from five independent plant lines were summed up, no error bars are shown this study. The result is in line with other publications describing MaWSD1 and MhWS1 as bifunctional WSD (Barney et al, 2012;Holtzapple and Schmidt-Dannert, 2007;Petronikolou and Nair, 2018). MaWSD3 did not show any activity when expressed in S. cerevisiae H1246.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As average values from five independent plant lines were summed up, no error bars are shown this study. The result is in line with other publications describing MaWSD1 and MhWS1 as bifunctional WSD (Barney et al, 2012;Holtzapple and Schmidt-Dannert, 2007;Petronikolou and Nair, 2018). MaWSD3 did not show any activity when expressed in S. cerevisiae H1246.…”
Section: Discussionsupporting
confidence: 92%
“…MaWSD5-his 6 had a higher WS activity with 18:1 OH compared to 18:0 OH and no WS activity was observed for saturated fatty alcohols of 20 carbons chain length or longer. This observation might be either explained by a different solubility of saturated and desaturated fatty alcohols which can affect the accessibility of the substrate for the enzyme or by spatial limitations of the fatty alcohol binding site (Barney et al, 2013(Barney et al, , 2015Petronikolou and Nair, 2018). The binding site might allow only the binding of fatty alcohols with a certain chain length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mutational analyses of bacterial WSD (Ma1; WP_011783747) from M. aquaeolei VT8 also showed that mutations of 25G, 144 A, 356L, 360A, and 405M sites could alter substrate selectivity to synthesize wax esters of different lengths ( Barney et al, 2013 , 2015 ; Petronikolou et al , 2018 ). However, 259T and 403A sites of SpWSD1 do not have corresponding positions in the Ma1 sequence due to absence of the corresponding structure Ma1 based on the pairwise alignment of the two gene sequences ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant expression analyses of WSD1 in yeast and Escherichia coli revealed predominant wax synthase functions, and showed that it could synthesize different wax ester products, including C34, C40, and C44, using different substrate combinations of primary alcohols and primary acids ( Li et al , 2008 ). The substrate selectivity of WS/DGAT enzymes from Marinobacter aquaeolei can be altered through mutations in specific residues, resulting in the synthesis of different wax ester components ( Barney et al, 2013 , 2015 ; Petronikolou et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%